2006
DOI: 10.1021/cg060228j
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Inorganic−Organic Hybrid Composite Solids Based on Molybdenum Oxide Chains

Abstract: Six inorganic-organic compounds based on [Mo x O y ] nchains, [Ag 2 (quinoxaline) 2 Mo 4 O 13 ] (1), [Cu 2 (DMPz) 2 Mo 4 O 13 ] (2) (DMPz ) 2,5-dimethylpyrazine), [Cu 2 (4-PBIM) 2 Mo 4 O 13 ] (3) [4-PBIM ) 2-(4-pyridyl)benzimidazole], [Cu(OPBIM)(H 2 O) Mo 3 O 10 ]‚H 2 O (4) [OPBIM ) 2-(2-ol-3-pyridinio)benzimidazole], [Co(3-HPBIM) 2 (H 2 O) 2 Mo 6 O 20 ] (5) [3-HPBIM ) 2-(3-pyridyl)benzimidazolium], [Ni(3-HPBIM) 2 (H 2 O) 2 Mo 6 O 20 ] (6), have been hydrothermally synthesized and characterized by single-cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 52 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…It was found that these characteristic peaks of CMC tend to be stronger as the content of the organic species increases. Meanwhile, the absorption around 500 cm −1 , which corresponds to inorganic molybdenum oxide [26][27][28], decreases when the composition of organic polymer increases.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that these characteristic peaks of CMC tend to be stronger as the content of the organic species increases. Meanwhile, the absorption around 500 cm −1 , which corresponds to inorganic molybdenum oxide [26][27][28], decreases when the composition of organic polymer increases.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the pure btb ligand, the origin of the emission for compound 1 can be tentatively attributable to a joint contribution of ligand-to-metal charge transfer (LMCT) (377 nm) and intraligand π* → π transitions of the neutral ligand (ca. 456 nm) [44,45]. What's worth mentioning is that the intensity of the strong emission band of 1 is obvious enhancement, which is attributed to an internal heavy metal effect.…”
Section: Inorganic Chemistry Communications J O U R N a L H O M E P Amentioning
confidence: 92%
“…For related structures, see: Alcade et al (1992); Chen et al (2006); Huang et al (2004); Wang et al (1999).…”
Section: Related Literaturementioning
confidence: 99%